Analisis Model Cash Waqf Linked Sukuk (CWLS) Sebagai Instrumen Pembiayaan Pemulihan Dampak Pandemi Covid-19: An Analysis of Cash Waqf Linked Sukuk (CWLS) Model as a Financing Instrument for Economic Recovery from Covid-19 Pandemic Impact - Muh Idhiel Fitriawan Rahman; Nurwahidin Nurwahidin; Naif Adnan (Jurnal Bimas Islam, 2021)
This research aims to analyze Cash Waqf Linked Sukuk (CWLS) potential as a financing instrument for recovering the Covid-19 pandemic impact in Indonesia. This research uses a descriptive qualitative approach by examining and analyzing facts, expert opinions, theories, and previous researches related to Cash Waqf Linked Sukuk (CWLS) and their potential development. This research finds that Cash Waqf Linked Sukuk can be an alternative sustainable Islamic financial instrument in Indonesia and it can be a source of funds for financing the economic impact due to Covid-19 pandemic. This instrument is very suitable because it has high flexibility, and it is attractive to the Muslim philanthropic middle class. Cash Waqf linked Sukuk also fulfills the conditions for financing the recovery of the Covid-19 pandemic, which requires short and medium-term financing. The Cash Waqf Linked Sukuk model as a source of financing for the recovery of the economic impact due to Covid-19 requires coordination between the Indonesian Waqf Board, the Ministry of Finance, the Implementer of the PEN Program, and organizations or institutions managing community funds to manage cash waqf funds.